Synthesis and evaluation of the NSCLC anti-cancer activity and physical properties of 4-aryl-N-phenylpyrimidin-2-amines - Toviwek, Borvornwat; Suphakun, Praphasri; Choowongkomon, Kiattawee; Hannongbua, Supa; Gleeson, M. Paul (My University, 2017)
Reported herein are efforts to profile 4-aryl-N-phenylpyrimidin-2-amines in terms of their anti-cancer activity towards non small-cell lung carcinoma (NSCLC) cells. We have synthesized new 4-aryl-N-phenylpyrimidin-2-amines and assessed them in terms of their cytotoxicity (A549, NCI-H187, MCF7, Vero & KB) and physicochemical properties (logD7.4 and solubility). 13f and 13c demonstrated potent anti-cancer activity in A549 cells (0.2 µM), compared to 0.4 μM for the NSCLC drug Doxorubicin. 13f also displayed low experimental logD7.4 (2.9) and the best solubility (∼40 μM). Compounds 13b and 13d showed the best balance of A549 anti-cancer activity and selectivity. 13g showed good activity and selectivity comparable with the anti-cancer drug Doxorubicin.
Keywords: A549; Computational design; Cytotoxicity; Lipophilicity; Solubility